Individuos y espacios domésticos: estrategias de transmisión de la propiedad de las mujeres viudas en la España rural (extremadura, siglo XVIII) - Tovar Pulido, Raquel (Studia Europaea Gnesnensia, 2019)
This article discusses the distribution of paternal property within rural communi-ties in the interior of the Iberian Peninsula, through an analysis of familial inher-itance of a widow from Extremadura. As a source for the study, the author draws on the Cadastre Ledger of the Marquis of Ensenada (1761), kept in the General Archive of Simancas (AGS), capturing changes in the family estate of a country widow (living in the village of Alcuéscar) in the mid-eighteenth century resulting from a transfer of property. Using the method of quantitative analysis developed by the Annales School, the author examines the issue from several standpoints; on the one hand, this enables insights into the increases and reductions in the volume of real estate (urban and rural) and the real estate assets of such women through pur-chases and sales. On the other, the author is also able to analyze and outline the distribution ofa widow’s property during her life and after her death.